Modelo do projetista e modelo do usuário no design de produtos: um estudo da atividade de lavar roupas - Medeiros, Marcella Hellen Rezende de (Universidade Federal de São Carlos, 2014)
In the product development process, user-related issues have achieved increasingly more relevance as they are progressively being perceived as strategies for innovation and competitiveness. In defining product specifications, designers strive to meet user needs. However, in real-use situations, a number of variability factors will result in gaps between what was anticipated by designers and actual user activity (DANIELLOU, 2002). This research was deployed during a laundry machine development process. The aim was to understand the existing gap between the designer model and the user model with regard to laundry activity, as well as user strategies to circumvent these gaps. Starting from the assumptions in Situated Ergonomics, we applied the activity analysis method. The results presented multi-determinants of the design process, such as: market needs; user knowledge; deadlines; financial resources; and project team member expertise. These determinants influenced the drafting of usage requirements, which, in real-use situations, reflected some gaps between designer and user models. Field research uncovered user strategies, such as: resorting to other information sources; creating new ways of use in line with user habits or interaction conditioned by their environment; and ignoring product functions they did not understand. This study's contributions relate to the importance of activity analysis in the design process and the role of the ergonomist in product design.
Keywords: Desenvolvimento de produtos; Ergonomia; Análise de atividade; Máquinas de lavar roupas; Produt design; User; Ergonomics; Activity analysis; ENGENHARIAS::ENGENHARIA DE PRODUCAO